A one-year pilot study comparing direct-infusion high resolution mass spectrometry based untargeted metabolomics to targeted diagnostic screening for inherited metabolic diseases - Willems, Anke P.; van der Ham, Maria; Schiebergen-Bronkhorst, Birgit G. M.; van Aalderen, Mirjam; de Barse, Martina M. J.; De Gruyter, Fini E.; van Hoek, Ilja N.; Pras-Raves, Mia L.; de Sain-van der Velden, Monique G. M.; Prinsen, Hubertus C. M. T.; Verhoeven-Duif, Nanda M.; Jans, Judith J. M. (Frontiers in Molecular Biosciences, 2023)
This is a provisional file, not the final typeset article Illustrating its potential, DI-HRMS detected additional patients with aberrant metabolites that were indicative of an IMD not detected by targeted plasma analysis, such as purine and pyrimidine disorders and a carnitine synthesis disorder.This one-year pilot study showed that DI-HRMS untargeted metabolomics can be used as a first-tier approach replacing targeted assays of amino acid, acylcarnitine and creatine metabolites with ample opportunities to expand. Using DI-HRMS untargeted metabolomics as a first-tier will open up possibilities to look for new biomarkers.